Reversible data hiding in encrypted images using recompression - Jiu-fen LIU; Tao HAN; Yu-guo TIAN; Wen-bin LIU (Tongxin xuebao)
To improve the performance of RDH (reversible data hiding) method in encrypted images,the embedding room was reserved before encryption and realizes the real separation of the data extraction from image decryption in op-eration.First,the feasibility of RDH in JPEG decompressed image blocks was researched.Then the theoretical probabil-ity of successful recovery of decompressed image blocks was calculated.Finally,a method of RDH in encrypted images was proposed and the main steps of the method include pretreatment,encryption,data embedding,data extraction and image recovery.The performance of the proposed method was compared with three existing RDH methods in encrypted images.The results demonstrate the proposed method has less error in image recovery,and for given embedding rates,the PSNR of decrypted image containing the embedded data are significantly improved.